Methods of Complex Dynamic Systems' Models' Equivalent Conversion - Verlan, A.; Sterten, Jo (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2020)
Proposed and considered the formal description of equivalent conversions which can be applied to obtain the various models of different kinds of complex dynamic systems (including electrical systems, power installations, etc.), as well as for transition from one representation to another. The set of basic operations which realize elementary conversions of models is described. The methods and algorithms for conversion of differential equations into integral or integro-differential are considered Запропоновано та розглянуто формальний опис еквівалентних перетворень, які можна застосувати для отримання різних моделей складних динамічних систем (включаючи електричні системи, енергоустановки тощо), а також для переходу від одного представлення до іншого. Описано набір основних операцій, які реалізують перетворення моделей. Розглянуто методи та алгоритми перетворення диференціальних рівнянь в інтегральні та інтегро-диференціальні.